The Communication of Ideas across Subfields in Political Science. Issue 2 (14th April 2014) - Graham, Erin R.; Shipan, Charles R.; Volden, Craig
ABSTRACT What factors inhibit or facilitate cross-subfield conversations in political science? This article draws on diffusion scholarship to gain insight into cross-subfield communication. Diffusion scholarship represents a case where such communication might be expected, given that similar diffusion processes are analyzed in American politics, comparative politics, and international relations. We identify nearly 800 journal articles published on diffusion within political science between 1958 and 2008. Using network analysis we investigate the degree to which three "common culprits"—terminology, methodological approach, and journal type—influence levels of integration. We find the highest levels of integration among scholars using similar terms to describe diffusion processes, sharing a methodological approach (especially in quantitative scholarship), and publishing in a common set of subfield journals. These findings shed light on when cross-subfield communication is likely to occur with ease and when barriers may prove prohibitive.